An orchestrator for dynamic interconnection of software components - Barbosa, L. S. (2007)
Composing and orchestrating software components is a fundamental concern in modern software engineering. This paper addresses the possibility of such orchestration being dynamic, in the sense that the structure of component's interconnection patterns can change at run-time. The envisaged approach extends previous work by the authors on the use of coalgebraic models for the specification of software connectors.